HISTORICAL AND PATRIOTIC PROJECT «LIFE-LONG MEMORY OF WAR» - Andrey N. Kustyshev; Oksana I. Belyaeva (Высшее образование в России)
The article presents the Republican noncommercial publishing historical and patriotic project «Life-long memory ofwar» initiated by Ukhta State Technical University. Several hundred students attended to the implementation of this project. The result of work is the publication of a multivolume collection of memoirs of participants of the Great Patriotic war - inhabitants of Komi Republic.